2022
DOI: 10.1186/s11658-022-00336-6
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 application in cancer therapy: a pioneering genome editing tool

Abstract: The progress of genetic engineering in the 1970s brought about a paradigm shift in genome editing technology. The clustered regularly interspaced short palindromic repeats/CRISPR associated protein 9 (CRISPR/Cas9) system is a flexible means to target and modify particular DNA sequences in the genome. Several applications of CRISPR/Cas9 are presently being studied in cancer biology and oncology to provide vigorous site-specific gene editing to enhance its biological and clinical uses. CRISPR's flexibility and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 334 publications
(284 reference statements)
0
11
0
Order By: Relevance
“…Cells in a state of hypoxia undergo anaerobic metabolism to produce energy to maintain metabolic activity. Due to the insufficiency of carbohydrates during the early stage of tumor tissue, cancer cells may activate FASN to produce long-chain fatty acids as an energy alternate for survival (39)(40)(41)(42). In contrast to original breast cancers that had metastasized to other places, a recent study indicated that FASN was more significantly expressed in breast tumors that had spread to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Cells in a state of hypoxia undergo anaerobic metabolism to produce energy to maintain metabolic activity. Due to the insufficiency of carbohydrates during the early stage of tumor tissue, cancer cells may activate FASN to produce long-chain fatty acids as an energy alternate for survival (39)(40)(41)(42). In contrast to original breast cancers that had metastasized to other places, a recent study indicated that FASN was more significantly expressed in breast tumors that had spread to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas9 system can modify elements of targeted DNA in a site-specific manner in live cells and, thus, drastically change the genome of tumors or other cells and acquire heritable phenotype. [850][851][852] For example, knocking down MDRassociated genes using CRISPR/Cas9 can bring edited cells resensitive to chemotherapeutic drugs and later generations. Given the characteristics of this system, CRISPR/Cas9-based gene-editing of tumor cells or tumor-associated cells hold more promising and effective therapeutic potential for cancer treatment (Figure 12C).…”
Section: Nps For Chemogene Therapymentioning
confidence: 99%
“…Moreover, RNA‐based gene‐silence therapy can only work temporally, necessitating frequent and long‐term treatment. CRISPR/Cas9 system can modify elements of targeted DNA in a site‐specific manner in live cells and, thus, drastically change the genome of tumors or other cells and acquire heritable phenotype 850–852 . For example, knocking down MDR‐associated genes using CRISPR/Cas9 can bring edited cells resensitive to chemotherapeutic drugs and later generations.…”
Section: Cancer Therapies Using Npsmentioning
confidence: 99%
“…These favorable effects were presumably caused by the overexpression of zonula occludens (ZO-1) and the downregulation of the primary regulator of EMT, zinc-finger Frontiers in Molecular Biosciences frontiersin.org E-box binding homeobox 1 (ZEB1) (Lee et al, 2018). Increasing TJ-associated protein expression and lowering ZEB1 activation reduces cell motility and invasiveness (Liu et al, 2019;Shojaei Baghini et al, 2022).…”
Section: Dclk1 Downregulation: Ongoing Clinical Trials Challenge and ...mentioning
confidence: 99%